Effect of Fragarin on the Cytoplasmic Membrane of the Phytopathogen Clavibacter michiganensis - Filippone, María Paula (2001)
Fragarin, an antibiotic that was isolated and purified from a soluble fraction of strawberry leaves, may be a new type of preformed antimicrobial compound (phytoanticipin). Here, we report that the growth and oxygen consumption of the phytopathogenic bacterium Clavibacter michiganensis were rapidly inhibited after the addition of fragarin to cultures. Also, dissipation of the membrane potential and an increase of cell membrane permeability were observed in the presence of fragarin. The ability of fragarin to dissipate the membrane potential was confirmed with the use of small unilamellar liposomes made with lipids extracted from C. michiganensis. Our results suggest that fragarin is able to act at the membrane level, and that this action is correlated with a decrease in cell viability.